A micro-mobility solution for supporting QoS in global mobility - Lopes, Nuno Vasco (2010)
Today, users want to have simultaneously mobility, Quality of Service (QoS) and be always connected to Internet. Therefore, this paper proposes a QoS micro-mobility solution able to provide QoS support for global mobility. The solution comprises enhancements in the mobility management of Mobile IPv6 (MIPv6) and in the resources management of Differentiated Services (DiffServ) QoS model. The mobility management of MIPv6 was extended with fast and local handovers to improve its efficiency in micro-mobility scenarios with frequent handovers. The DiffServ resource management has been extended with adaptive and dynamic QoS provisioning to improve resources utilization in mobile IP networks. Further, in order to improve resources utilization the mobility and QoS messages were coupled, providing a resource management able to, proactively, react to mobile events. The performance improvement of the proposed solution and the model parametrization was evaluated using a simulation model. Simulation results indicate that the solution avoids network congestion and starvation of less priority DiffServ classes. Moreover, the results also indicate that bandwidth utilization for priority classes increases and the QoS offered to MN's applications, in each DiffServ class, keeps up unchangeable with MN mobility.